Music in words: A guide to researching and writing about music - Herbert, Trevor (Oxford Oxford university press, 2001)
"'... excellent resource... essential reading at first-degree or diploma level... I cannot recommend this volume highly enough... one of the most valuable books available in today's commercial market.' John Woodford www.musicteachers.co.uk September 2001 'It can be recommended to anyone needing to write about music and is full of good advice.' Early Music Review October 2001 '...a commendably thorough survey... Clearly expressed and logically ordered, Herbert's concise guide offers helpful, common-sense advice... it will serve as an invaluable reference tool...' The Strad Dec 2001 'Thorough, readable and useful' Piano Nov/Dec 2001 'Well-written and easy to read... I can commend this volume to anyone considering undertaking further professional development in music.... an accessible and thorough source of guidance... a useful reference tool.' Ensemble (MMA) Sept 2001 'illuminating and often witty narrative... For the student and aspiring scholar, this is life-saving stuff... For its ideas and information, music students, performers and writers of all types should treasure this book... a most worthwhile reference work.' EPTA Piano Journal Spring 2002 'a most worthwhile reference work' Arietta Spring 2002 'The conception of this book is an inspiration.. the content is of the high standard most of us have come to expect of the Associated Board.' Choir & Organ March/April 2002 'an indispensable reference manual for any musician' Editor's Choice - CASS Spring 2002 'presented with impeccable clarity' Music Teacher March 2002 'not only a valuable quick-reference compendium of information but also a lively and enjoyable book that triggers as well as offers ideas.' Australian Music Teacher Magazine May-June 02 'should become the standard reference work for all serious writers about music.' The Trombonist Autumn 2002 '...packed with practicalities, ideally suited to the needs of the undergraduate and postgraduate student... valuable reference book' South African Music Teacher 2003"